The Impact of Globalization on European Airline Market - Anastasiia Kuz; Algirdas Miskinis (Ekonomika, 2021)
Airline industry is very important for modern society as the biggest player in the globalization process by connecting regions, promoting global trade and tourism, facilitating economic and social development. However, here is a lack of research on relationship between globalization and airline industry in Europe. It remains unclear how to measure the impact of globalization on performance of airline companies and industry. The article aims at investigation of the impact of globalization on operational and financial performance of European airlines before pandemics. The authors applied a nonexperimental quantitative research design to analyze the relationship between independent globalization variables (level of globalization in Europe, globalization opportunity, globalization threat) and dependent airlines’ operational and financial performance indicators. Research is done using secondary data from annual reports of 19 European airlines members of European Common Aviation Area (ECAA). The panel data analysis was applied for 2007–2017 with multiple regression analysis using STATA. The results show that globalization exerts a significant positive effect on operational performance. On financial performance only revenue per passenger kilometers is positively influenced by globalization. Globalization affects low-cost airlines and full-service airlines performance differently.